Pulmonary Tumor Thrombotic Microangiopathy: A New Paraneoplastic Syndrome? - Carter, Corey A. (Case Rep Oncol, 2016)
This report, based on data from a clinical case, proposes that pulmonary tumor thrombotic microangiopathy, an underdiagnosed cause of pulmonary hypertension and death in patients with adenocarcinoma, is a paraneoplastic syndrome (PNS). Clinicians in general must be alert to the presence or development of PNS that may precede, coincide with, follow, or herald the recurrence or the primary diagnosis of malignancy since early recognition facilitates prompt diagnosis and treatment.